2018
DOI: 10.1177/1091581818800020
|View full text |Cite
|
Sign up to set email alerts
|

Safety Assessment of Rosmarinus officinalis (Rosemary)-Derived Ingredients as Used in Cosmetics

Abstract: The Cosmetic Ingredient Review Expert Panel (Panel) assessed the safety of 10 Rosmarinus officinalis (rosemary)-derived ingredients and concluded these ingredients are safe as used in cosmetics when formulated to be nonsensitizing. The R officinalis-derived ingredients are most frequently reported to function in cosmetics as skin conditioning agents or as fragrance ingredients. The Panel reviewed the available animal and clinical data to determine the safety of these ingredients. Because final product formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Despite that several studies have demonstrated that 0.1% rosemary leaf extract applied topically could cause skin erythema, our data contradicted with their results [ 50 , 51 ]. Moreover, Monice et al stated that it is safe to use rosemary leaf extract up to the 10 mL/kg and the pretreatment with 10 to 1000 µg/cm 2 of the rosemary extract could significantly reduce ear edema caused by 25 ng/cm 2 of 12-tetradecanoylphorbol-13-acetate in mice [ 52 ]. All the participants of the current study had negative reaction according to the International Contact Dermatitis Research Group criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Despite that several studies have demonstrated that 0.1% rosemary leaf extract applied topically could cause skin erythema, our data contradicted with their results [ 50 , 51 ]. Moreover, Monice et al stated that it is safe to use rosemary leaf extract up to the 10 mL/kg and the pretreatment with 10 to 1000 µg/cm 2 of the rosemary extract could significantly reduce ear edema caused by 25 ng/cm 2 of 12-tetradecanoylphorbol-13-acetate in mice [ 52 ]. All the participants of the current study had negative reaction according to the International Contact Dermatitis Research Group criteria.…”
Section: Resultsmentioning
confidence: 99%
“…They also reported six chemotypes depending on the dominant molecule and another six intermediates for the same genotype [51]. Fiume et al [49] confirmed that the amount of carnosol and carnosic acid present in the extract varies with the method of extraction. The level of carnosol and carnosic acid found in a rosemary extract prepared from a partially deodorized ethanol extract of rosemary is between 5% and 7%, whereas in an extract prepared with supercritical carbon dioxide, the level increases up to 30%.…”
Section: Phenolic Acidsmentioning
confidence: 89%
“…Fiume et al [49] found, in a study conducted in the United States, that rosemary can be observed in 729 formulations. Its essential oil (usually used in fragrances) and leaf extract (as a skin conditioner) were found to have 474 and 404 uses, respectively.…”
Section: Use Of Rosemary In Food and Cosmetics And Examples Of Othermentioning
confidence: 99%
See 1 more Smart Citation
“…Rosemary extracts have been proposed and used as bioactive, antioxidant additives in food, cosmetics, packaging, etc. [ 48 , 49 , 50 , 51 , 52 ]. Their worldwide market is expected to present an annual growth rate of roughly 3.7% over the next five years, and will reach 260 million US$ in 2024 from 210 million US$ in 2019 [ 53 ].…”
Section: Rosemarymentioning
confidence: 99%